2018
DOI: 10.1007/s40502-018-0400-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation interception, extinction coefficient and use efficiency of wheat crop at various irrigation and nitrogen levels in a semi-arid location

Abstract: Field experiments were conducted to study the effect of irrigation and nitrogen levels on radiation use efficiency (RUE), radiation extinction coefficient (κ) and temporal variation of leaf area index (LAI) and fraction intercepted photosynthetically active radiation (fIPAR). The LAI of wheat increased with increase in irrigation and nitrogen levels. The fIPAR also followed trend similar to LAI. The LAI and fIPAR showed logarithmic relationship with R2 value of 0.92 and 0.93 for the years 2013–2014 and 2014–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 49 publications
9
23
0
1
Order By: Relevance
“…Besides measuring agronomic traits, we also used NDVI measurements, a nondestructive and heritable method which provides information on leaf area and radiation intercepted by the canopy [65,66]. Monitoring NDVI all along the plant development allowed us to model the different phases and to identify "stay green" varieties, i.e., those with a delayed senescence, a trait that has been shown to impact positively yield in pure lines [34].…”
Section: Discussionmentioning
confidence: 99%
“…Besides measuring agronomic traits, we also used NDVI measurements, a nondestructive and heritable method which provides information on leaf area and radiation intercepted by the canopy [65,66]. Monitoring NDVI all along the plant development allowed us to model the different phases and to identify "stay green" varieties, i.e., those with a delayed senescence, a trait that has been shown to impact positively yield in pure lines [34].…”
Section: Discussionmentioning
confidence: 99%
“…The RUE of the seasonal changes (i.e., temporal) was calculated as the difference in the total crop dry weight between two consecutive measurements divided by the corresponding amount of PAR intercepted [10][11]. The seasonal mean RUE was computed as the slope of the linear regression of the cumulative biomass plotted against the corresponding amount of PAR intercepted [9].…”
Section: Computation Of Radiation-use Efficiency (Rue)mentioning
confidence: 99%
“…This was due to greater LAI during these two growth stages. It was reported that higher PAR interception in wheat due to greater LAI [30].…”
Section: Seed Yield In Spring -Summer and Rainy Seasonmentioning
confidence: 99%
“…The LAI has an immense importance in capturing the radiation falling over the canopies [22,30]. The foliage structure, canopy architecture and cloud condition regulate the availability of solar radiation to the crop canopy [31,32].…”
Section: Seed Yield In Spring -Summer and Rainy Seasonmentioning
confidence: 99%